Electrocaloric effect and freezing temperature in (Pb0.8Ba0.2)[(Zn1∕3Nb2∕3)0.7Ti0.3]O3 relaxor ferroelectric ceramic - A. Peláiz-Barranco; F. Calderón-Piñar; Y. Mendez-González (Journal of Advanced Dielectrics, 2016)
The electrocaloric effect (ECE) is studied in (Pb0.8Ba0.2)[(Zn1∕3Nb2∕3)0.7Ti0.3]O3 relaxor ferroelectric ceramic by using an “indirect method”. The electric dependence for the polarization (hysteresis loops) has been obtained for several temperatures showing typical relaxor characteristics. The temperature change ΔT, which is associated with the ECE, is calculated by using the temperature dependence for the polarization. A maximum value for ΔT is observed for temperatures close above the freezing temperature, showing an indirect evidence of that critical temperature. The results are discussed considering the contribution of the polar nanoregions to the polarization.